2016
DOI: 10.1093/ejcts/ezw100
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral internal mammary artery grafting:in situversus Y-graft. Similar 20-year outcome

Abstract: The clinical outcome of BIMA grafting is independent of surgical configuration. Y-grafting increases the flexibility of BIMA grafting and should be taken into account when a surgical strategy for myocardial revascularization needs to be planned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 25 publications
3
18
1
2
Order By: Relevance
“…Although previous studies have shown no difference in long-term survival or freedom from repeat revascularization between different BITA configurations [12][13][14][15][16][17][18][19][20], and although those studies have also shown that no particular configuration is associated with relatively favorable clinical outcomes, our study revealed that certain aspects of the configuration must be considered. The selection of the ideal BITA configuration should be based on technical factors associated with the individual patient.…”
Section: Kjtcvscontrasting
confidence: 83%
“…Although previous studies have shown no difference in long-term survival or freedom from repeat revascularization between different BITA configurations [12][13][14][15][16][17][18][19][20], and although those studies have also shown that no particular configuration is associated with relatively favorable clinical outcomes, our study revealed that certain aspects of the configuration must be considered. The selection of the ideal BITA configuration should be based on technical factors associated with the individual patient.…”
Section: Kjtcvscontrasting
confidence: 83%
“…Also, BIMA could be performed using two different configurations, in situ versus Y-graft. A recent study evaluated whether graft configuration might affect long-term outcomes in 2150 patients using a propensityscore approach [18] . Late mortality and incidence of MACCES were similar between groups, and therefore the clinical outcome of BIMA grafting is independent of surgical configuration.…”
Section: Discussionmentioning
confidence: 99%
“…Late mortality and incidence of MACCES were similar between groups, and therefore the clinical outcome of BIMA grafting is independent of surgical configuration. However, Y-grafting increases the flexibility of BIMA grafting and should be taken into account when a surgical strategy for myocardial revascularization needs to be planned [18] .…”
Section: Discussionmentioning
confidence: 99%
“…Tatoulis et al [24] declared that the entire of perfusion time and cross clamp time needed in VCABG is longer than in TACABG. Di Mauro et al [25] stated that, graft configuration can influence the long-term outcomes by the use of a propensity-score approach. They also found that, the rate of MACCES and sudden mortality was not difference between studied groups, and also, configuration of the surgery doesn’t affect BIMA grafting.…”
Section: Discussionmentioning
confidence: 99%